(untitled) (Conferencea, 2022)
Speaking is the one type of productive skills but in order to communicate in a target language listening (a receptive skill) is also increasingly important when having a conversation. There are many factors to consider with teaching speaking. This essay will examine three main factors: cultural, learning and L1 factors. It is important to understand that many cognitive processes are taking place when a student speaks in the target language and so fluency can be a key focus when improving the skill.